Association of cardiac and renal function with extreme N-terminal fragment Pro-B-type natriuretic peptide levels in elderly patients - Cui Hua; Huo Guoliang; Liu Lin; Fan Li; Ye Ping; Cao Jian; Bai Yongyi; Wang Fan; Hu Yixin (BMC Cardiovascular Disorders, 2012)
Abstract Background The data are inconsistent regarding whether extreme N-terminal fragment pro-B-type natriuretic peptide (NT pro-BNP) levels are associated with impaired renal function. Furthermore, the relationship between extreme NT pro-BNP levels and cardiac and renal function in elderly patients has not been reported. The aim of the present study was to examine a hypothesis that extreme NT pro-BNP levels may be associated with impaired cardiac and renal function in elderly patients. Methods We retrospectively analyzed the data of demographic, clinical, and echocardiographic features on 152 consecutive elderly patients aged more than 80 years old (average age, 83.65 ± 3.58 years) with NT pro-BNP levels ≥ 3000 pg/ml. The participants were divided into two categories according to their NT pro-BNP levels: (1) 3000–10000 pg/mL and (2) >10000 pg /mL. Results The number of patients with impaired renal function (P = 0.019) and the mortality (P < 0.001) in the period of inpatient was higher in the group with NT pro-BNP > 10000 pg /mL. The levels of serum creatinine and creatine kinase MB (CK-MB) in the group of NT pro-BNP > 10000 pg / mL were higher than those in the group of NT pro-BNP = 3000-10000 pg/mL (P = 0.001 and P = 0.023, respectively). Furthermore, no significant difference in the distribution by NYHA class in different NT pro-BNP levels was observed. Multiple linear regression analyses demonstrated that with NT pro-BNP levels as the dependent variable, NT pro-BNP levels were positively correlated with CK-MB (β = 0.182, P = 0.024) and creatinine levels (β = 0.281, P = 0.001). The area under the receiver-operating characteristic (ROC) curve of NT pro-BNP levels and clinical diagnosis of impaired renal function was 0.596 and reached significant difference (95%CI:0.503-0.688, P = 0.044). Conclusion These data suggest that the extreme elevation of NT pro-BNP levels (≥3000 pg/ml) is mainly determined by impaired renal function in elderly patients above 80 years. Extreme NT pro-BNP levels may be useful for assessing the severity of impaired renal function.